The Influence of Problem Based Learning Model and Learning Motivation to Expository Writing Text Ability of Students Grade VII MTsN 1 Bukittinggi - Yendrawaty Yendrawaty (Jurnal Aplikasi IPTEK Indonesia, 2019)
This research aimed to describe the influence of Problem Based Learning Model and Learning Motivation to Expository Text Writing Skills of Students Grade VII MTsN Bukittinggi. The type of research is quasi experiment and the design used is factorial design 2x2. Sampling is done by purposive sampling. Data analysis and discussion were conducted through descriptive-analysis. The analysis results of data were as follows. First, writing expository text taught using the Problem Based Learning model is better than students taught by conventional learning models. Second, Second, writing the expositional text of students who have high learning motivation taught by using Problem Based Learning model is better than those taught with conventional learning model. Third, writing the expositional text of students who have low learning motivation taught by using Problem Based Learning model is better than those taught with conventional learning model. Fourthly, there is no interaction between learning motivation and the learning model in influencing the ability to write expository text of students. In the next description, PBL is used for Problem Based Learning.